Relationships between Fibrinolytic and Inflammatory Parameters in Human Adipose Tissue: Strong Contribution of TNFα Receptors to PAI-1 Levels - Bastelica, Delphine; Mavri, Alenka; Verdier, Monique; Berthet, Bruno; Juhan-Vague, Irène; Alessi, Marie-Christine (Thrombosis and Haemostasis, 2002)
Plasminogen activator inhibitor type 1 (PAI-1), a risk marker of atherosclerosis, is highly expressed in adipose tissue from obese subjects. PAI-1 is also considered as an acute phase protein. Recently, adipose tissue has been described as a source of inflammatory cytokines. Therefore, our aim was to study the relationships between PAI-1, and IL-6, TNF, TNF receptors (TNFRSF1s) and TGFβ1, in plasma and adipose tissue from obese (n = 60) and lean (n = 28) subjects. Study has been extended to plasminogen activators (t-PA and u-PA).Compared to lean subjects, obese subjects exhibited higher plasma levels of all the studied parameters (except for TGFβ1) whereas in adipose tissue only PAI-1, t-PA and TGFβ1 antigen levels differed. In the obese population, plasma PAI-1 levels were weakly associated with circulating TNF, and this relationship disappeared after adjustment for plasma t-PA. Adipose tissue PAI-1 levels were positively associated with TNFRSF1s and TGFβ1, the strongest relationship being observed with TNFRSF1A, which explained 82% of PAI-1 variability. TNF and IL-6 were the main contributors to t-PA variability in plasma and in adipose tissue, respectively.Our results argue on the relevance of TNFRSF1s in the regulation of PAI-1 expression by adipose tissue. Association between t-PA, which is mainly produced by endothelial cells, and IL-6 or TNF suggest that inflammation might be involved in angiogenesis in adipose tissue.Abbreviations: act: activity; ag: antigen; BMI: Body mass index; IL-6: Interleukin-6; PAI-1: plasminogen activator inhibitor type 1; TGFβ1: Transforming Growth Factor beta 1; TNF: Tumor Necrosis Factor alpha; TNFRSF1A and 1B: Tumor Necrosis Factor receptor superfamilly 1A and 1B (TNFRI and II respectively); t-PA: tissue type plasminogen activator; u-PA: urokinase type plasminogen activator
Keywords: Human adipose tissue; PAI-1; Plasminogen activators; Inflammatory cytokines